2022
DOI: 10.3390/plants11091130
|View full text |Cite
|
Sign up to set email alerts
|

Priming Treatments with Biostimulants to Cope the Short-Term Heat Stress Response: A Transcriptomic Profile Evaluation

Abstract: Plant stress induced by high temperature is a problem in wide areas of different regions in the world. The trend of global warming is going to enhance the effects of heat stress on crops in many cultivation areas. Heat stress impairs the stability of cell membranes and many biological processes involving both primary and secondary metabolism. Biostimulants are innovative agronomical tools that can be used as a strategy to counteract the detrimental effect of abiotic stresses, including heat stress. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In this study, endoplasmin and chaperonin CPN60-like were upregulated in the barley root-treated plants; however, heat shock protein (HSP 70) and small heat shock protein (sHSP) were downregulated. These results were consistent with those reported previously [ 64 ]. These authors noted that biostimulants based on Ascophyllum nodosum extracts (named Phylgreen) and based on animal L-amino acids (named Delfan Plus) induced the expression of some HSPs under control conditions, suggesting that they play a role during plant development, while other HSPs such as HSP 70 and small heat shock protein (sHSP) were upregulated under heat stress, suggesting that they perform a protective function against abiotic stress including heat stress.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, endoplasmin and chaperonin CPN60-like were upregulated in the barley root-treated plants; however, heat shock protein (HSP 70) and small heat shock protein (sHSP) were downregulated. These results were consistent with those reported previously [ 64 ]. These authors noted that biostimulants based on Ascophyllum nodosum extracts (named Phylgreen) and based on animal L-amino acids (named Delfan Plus) induced the expression of some HSPs under control conditions, suggesting that they play a role during plant development, while other HSPs such as HSP 70 and small heat shock protein (sHSP) were upregulated under heat stress, suggesting that they perform a protective function against abiotic stress including heat stress.…”
Section: Discussionsupporting
confidence: 94%
“…In AnE, the upregulation of defense pathway genes such as PinII (jasmonic acid), Etr1 (ethylene), and PR-1a (salicylic acid) enhanced the auxin-responsive proteins such as SAUR21 and indole-3-acetic acid-amido synthetase in AnE-treated tomatoes [172]. It was observed that the AnE alleviated the effect of heat stress by activating heat shock proteins (HPS), which mainly influenced the AtHSP17 family, particularly AtHPS17.4 and AtHPS17.6A and B, confirming the most significant changes [173].…”
Section: Solanum Lycopersicum Tomatomentioning
confidence: 81%
“…A possible agronomic management measure for crops is the exploitation and exploration of the microbiota in agroecosystems in symbiosis with crop plants. Multiple benefits are underlined by this innovative strategy, such as coping with biotic and abiotic stressesfor instance, heat stress [136,137], drought [138,139], waterlogging [140,141], and the attack of pests [142] and diseases [143,144].…”
Section: The Microbiomementioning
confidence: 99%